2021
DOI: 10.3390/ijerph18031243
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 Activity in the Brain: Simultaneous Effects on Energy Homeostasis and Reproduction

Abstract: Diet deeply impacts brain functions like synaptic plasticity and cognitive processes, neuroendocrine functions, reproduction and behaviour, with detrimental or protective effects on neuronal physiology and therefore consequences for health. In this respect, the activity of metabolic sensors within the brain is critical for the maintenance of health status and represents a possible therapeutic target for some diseases. This review summarizes the main activity of Sirtuin1 (Sirt1), a metabolic sensor within the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 136 publications
(189 reference statements)
0
17
0
Order By: Relevance
“…Resveratrol, curcumin, quercetin, tannins, and catechins may also be cited as molecules that increment sirtuins' actions [120][121][122]. Resveratrol has been found to ameliorate brain health through numerous signaling pathways mechanisms through Sirt-1.…”
Section: Polyphenols and Sirt-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol, curcumin, quercetin, tannins, and catechins may also be cited as molecules that increment sirtuins' actions [120][121][122]. Resveratrol has been found to ameliorate brain health through numerous signaling pathways mechanisms through Sirt-1.…”
Section: Polyphenols and Sirt-1mentioning
confidence: 99%
“…Chronic treatments with catechins, polyphenols present in many dietary foods, as gooseberries, apples, grape seeds, blueberries, strawberries, kiwi, red wine, green tea, cocoa, beer, cacao liquor, and chocolate, increase hippocampal Sirt-1 levels improving cognition in aged rats [125]. Therefore, polyphenols may defend Sirt-1 due to their antioxidant abilities and, in turn, moderate proteins affected by Sirt-1 action [122].…”
Section: Polyphenols and Sirt-1mentioning
confidence: 99%
“…Notably reproduction is under the control of the hypothalamus-pituitary-gonadal (HPG) axis and finds the main actors in the hypothalamic gonadotropin releasing hormone (GnRH), pituitary gonadotropins and sex steroids [74]. Many environmental factors, from nutritional cues, drug abuse, stressors or environmental pollutants, among others, affect reproduction at multiple levels along the HPG axis, with consequences for gamete quality, successful reproduction, embryo development and offspring health, as previously reviewed [75][76][77][78][79]. In this respect, in spite of the relative safety of glyphosate, in-vivo and in-vitro studies involving different organisms and cell types reported various adverse effects on reproduction (Figure 4), but several controversies concern chemical composition (glyphosate alone or in formulation), doses and exposure windows.…”
Section: Effects Of Glyphosate On Reproduction and Developmentmentioning
confidence: 99%
“…Interestingly, the Sirtuin 1 (Sirt1), the nuclear NAD + -dependent class III deacetylase, is an epigenetic target of environmental exposure to toxicants [ 27 ], being directly involved in coupling the cellular metabolic status (via NAD + ) to the modulation of both chromatin structure and gene expression with mechanisms involving the deacetylation of histone proteins or non-histone proteins like transcription factors, co-factors, or nuclear receptors (i.e., FOXO-1, p53, Nf-kb, PGC1-α, AR, ERα, LXRa, etc.) [ 28 , 29 ]. Sirt1, also known as the “longevity gene”, protects cells against apoptosis and inflammation and is involved in the control of cell proliferation, differentiation, or death and has gained considerable attention in epigenetic mechanisms [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sirt1, also known as the “longevity gene”, protects cells against apoptosis and inflammation and is involved in the control of cell proliferation, differentiation, or death and has gained considerable attention in epigenetic mechanisms [ 30 ]. Changes in Sirt1 expression are critical in several diseases, such as cardiovascular diseases, metabolic syndrome, cancer, neurodegeneration, and infertility [ 29 , 31 , 32 , 33 , 34 , 35 ]. In the liver, Sirt1 is involved in the control of both glucose and lipid metabolism [ 36 , 37 ] with different downstream pathways, including histone modification in the nucleus or p53 dependent apoptotic pathways aimed at counteracting the accumulation of hepatic oxidative stress and inflammation [ 37 ].…”
Section: Introductionmentioning
confidence: 99%